Efforts for improving buildings conditions in public schools in Egypt : SWOT analysis of two governmental renovation programs - Ibrahim, Nagwa (AUC Knowledge Fountain, 2017)
The buildings conditions of public schools are a key component of Egypt's education reform plan. Recently, the Ministry of Education introduced a number of reforms to improve the public schools conditions. These reforms include renovation programs focusing on solving all the damages inside public schools and make them safe for the students. This study relies on qualitative research methods through structured and semi-structured in-depth interviews with several ranks in the education sector for schools improvement .Interviews covered those people involved in two governmental renovation programs, which are the One Hundred Schools Development Program and the National Renovation Program including supervising engineers, managers of the programs as well as teachers and contractors involved in both programs. This study applied the SWOT analysis technique to analyze the two programs effectively. Findings demonstrate that both programs had many strengths and opportunities which are mainly in renovating schools buildings, providing technology tools and following strategic planning; however, there are serious weaknesses and threats that should be avoided in any coming school development program such as the limited number of labors and the insufficient budget. The study recommends having good time management, well developed strategic plan, regular documentation, depending on institutions and regular maintenance of the renovated buildings.